EFFECT OF DIRECT AND INDIRECT PRE-OXIDATION OF GOLD ORE FROM DOUP NORTH SULAWESI USING OZONE GAS ON THE GOLD EXTRACTION DURING CYANIDATION PROCESS - Chrisna, Chanovanto
Refractory gold ore is a type of gold ore that is difficult to process and produces gold recovery <95%, even <50% for the highly refractory category, when dissolved in conventional cyanidation. Gold recovery can be improved by pre-treatment of sulfide-type refractory gold ores where the gold grains are encapsulated in difficultto- dissolve sulfide minerals. One of the pre-treatment methods that may be applied is the use of ozone gas as an oxidizing agent. Ozone has a high standard reduction potential, which is +2.07 V (vs SHE), which can be produced from pure oxygen gas or air. In this study, gold ore samples from Doup, North Sulawesi were used to study the effect of direct and indirect pre-oxidation using ozone gas on the increasing gold recovery in the subsequent cyanidation process.